Amelanchier medik. (Rosaceae) Fruits – A Nutrition Dietary Product and a Source Material for Phytopharmacology - Kuklina, Alla; Sorokopudov, Vladimir; Stepanova, Anna (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Fruits of Amelanchier spicata (Lam.) K.Koch, Amelanchier alnifolia (Nutt.) Nutt.), Amelanchier florida Lindl., Amelanchier canadensis (L.) Medik. and Amelanchier laevis Wieg. (Rosaceae) are rich in ascorbic acid (up to 30.3 mg%), total sugar (up to 8.7%), they are also saturated with bioflavonoids, among which there are anthocyanins (353.1–608.2 mg%), possessing antioxidant qualities. Amelanchier fruits are the nutritious dietary product, in which the content of acids and sugars is balanced. They are suitable for various types of processing and can serve as phytopharmacological raw materials. Biochemical analysis of leaves of Amelanchier spicata and Amelanchier alnifolia showed that they are enriched with bioflavonoids (260–370 mg%), which is also valuable for phytopharmacology. Amelanchier alnifolia and closely related Amelanchier florida have especially large and delicious fruits, more enriched with saccharides and anthocyanins. They have prospects for a further selection as a highly productive garden and food culture. Amelanchier laevis plants luxuriantly bloom, but they differ in an irregular fruit bearing and smaller fruits (0.6 g in weight), they are promising as an ornamental culture.